Scholar Failure: From the University Students’ Perception - Jade Isabel, Damián-Notario; Esteban, Torres-Zapata Ángel; Javier, Rivera-Domínguez; Rafael, Villanueva Echavarría José; Eduardo, Moguel-Ceballos Juan (International Journal of Educational Studies, 2020)
Scholar failure, defined as the insufficient quantitative performance of the students’ potential which impedes them to achieve the minimum parameters stablished by an educative institution, generating in the student a feeling of letdown, and low performance, becoming a prelude to educational lagging and school dropout. The goal of this research was to determine the reasons of academic failure from the student perspective. This is a descriptive, cross-sectional study, with a non-probabilistic by convenience sampling, 66 students participated on it, who failed on at least one course on the August – December 2019 scholar period. The instrument applied gathers information such as: Name, gender, age, enrollment code, cycle, and the following question: Which do you consider where the reasons for your academic failure? The answers where later classified as follows 1) inherent to the student 2) inherent to the teacher, 3) inherent to the family or the family’s economy 4) inherent to the curricula, and 5) inherent to the institution. Results show that the two main reasons of academic failure from a student’s perspective are inherent to the student (49.5%) and inherent to the teacher (26.6%). These results, allow to determine analysis and opportunity zones that must be addressed to reduce the scholar failure and school dropout rates.